Seed freeze sensitivity and ex situ longevity of 295 species in the native Hawaiian flora. Issue 9 (9th September 2019) - Chau, Marian M.; Chambers, Timothy; Weisenberger, Lauren; Keir, Matthew; Kroessig, Timothy I.; Wolkis, Dustin; Kam, Roy; Yoshinaga, Alvin Y.
Abstract : Premise: Ex situ seed banking is critical for plant conservation globally, especially for threatened floras in tropical ecosystems like Hawai'i. Seed bank managers must maximize longevity, and species managers must plan restoration before seeds lose viability. Previous observations suggested some native Hawaiian seeds lost viability in frozen storage (−18°C). We investigated seed storage behavior in the Hawaiian flora to optimize storage conditions and recommend re‐collection intervals (RCI) to maximize viability of stored seeds. Methods: Using 20+ years of real‐time seed storage viability data, we tested freeze sensitivity for 197 species and calculated RCIs for 295 species. Using paired tests of accessions stored >2 yr at 5°C and −18°C, we developed an index of relative performance to determine freeze sensitivity. We calculated RCIs at 70% of highest germination (P70). Results: We identified four families (Campanulaceae, Cyperaceae, Rubiaceae, and Urticaceae) and four genera with seed freeze sensitivity and six additional genera with likely freeze sensitivity. Storage longevity was variable, but 195 species had viability >70% at the most recent tests (1 to 20+ yr), 123 species had RCIs >10 yr, and 45 species had RCIs <5 yr. Conclusions: Freeze sensitive storage behavior is more widely observed in Hawai'i than any other regional flora, perhaps due to insufficient testing elsewhere. We present a new protocol to test seed freeze sensitivity, which is often not evident until 2–5 years of storage. Re‐collection intervals will guide restoration practices in Hawai'i, and results inform seed conservation efforts globally, especially tropical and subtropical regions.